The Implementation of Educational Services for Students with Special Needs in Primary School - Zaini Hafidh; Nabila Salma Meirani; Revi Novaliani Hermansyah; Nazwa Rifqha Aisyah (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
This study analyzes the implementation of inclusive education services, which continue to face various challenges, including limited teacher competence, inadequate supporting facilities, adaptive curriculum constraints, and difficulties in meeting the learning needs of students with special needs. The purpose of this study is to examine the implementation of educational services for students with special needs at SP3I Primary School, SDN 093 Tunas Harapan Cijerah. This research employed a qualitative approach using a case study method. Data collection techniques included semi-structured interviews with teachers, observations, and document analysis, such as Individual Learning Implementation Plans and the Individual Adaptive Curriculum for Students. The findings reveal that SDN 093 has implemented the SP3I model continuously since 2005 through the establishment of the SP3I Team and Special Assistant Teachers, curriculum adjustments using individualized lesson plans that simplify learning materials with illustrations, as well as social-emotional development programs involving daily life skills and religious activities. These efforts have contributed to the development of an empathetic culture among students. Nevertheless, the main challenges include limited disability-friendly infrastructure, insufficient learning aids for students with physical and visual impairments, and increased teacher workload due to minimal support from the another stakeholders. This study highlights the importance of internal school support in ensuring the sustainability of inclusive education. Furthermore, it provides an overview of the implementation of inclusive education at the elementary school level, particularly under conditions of limited resources, and is expected to serve as a reference for schools and policymakers in strengthening support for inclusive education services.